Rescue of Drosophila labial null mutant by the chicken ortholog Hoxb-1 demonstrates that the function of Hox genes is phylogenetically conserved. - Lutz, B.; Lu, H.C.; Eichele, G.; Miller, D.; Kaufman, T.C. (Genes & Development, 1996)
Hox complexes are important players in the establishment of the body plan of invertebrates and vertebrates. Sequence comparison demonstrates a remarkable phylogenetic conservation of key structural features of Hox genes. The correlation between the physical order of genes along the chromosomes and their domains of function along the body axis is conserved between arthropods and vertebrates. Ectopic expression experiments suggest that the functions of homeo proteins also are conserved between invertebrates and vertebrates. However, it remains an open question whether vertebrate Hox genes expressed under the control of Drosophila regulatory sequences can substitute the function of Drosophila Hox genes. We have studied this issue with the Drosophila labial (lab) gene and its chicken ortholog gHoxb-1. We fused the entire protein-coding region of gHoxb-1 with previously identified regulatory sequences of lab. This approach places gHoxb-1 into the normal embryonic spatiotemporal context in which lab acts. Ten transgenic lines carrying gHoxb-1 were established and tested for their ability to rescue lab null mutant animals. Eight lines rescued with high efficiency, embryonic lethality, and abnormal head morphogenesis, two defects observed in lab null mutant embryos. The rescue with the gHoxb-1 minigene was close to the efficiency of that obtained with the Drosophila lab minigene. This indicates that gHoxb-1 protein can regulate lab target genes and thereby restore embryonic viability. This is striking, as Lab and gHoxb-1 proteins are divergent except for their homeo domains and a short stretch of amino acids amino-terminal to the homeo domain. Our findings demonstrate a functional conservation of the lab class homeo proteins between insects and vertebrates and support the view that function of Hox genes resides in relatively few conserved motifs and largely in the homeo domain.